Efficient ABAC based information sharing within MQTT environments under emergencies. Issue 120 (September 2022) - Colombo, Pietro; Ferrari, Elena; Tümer, Engin Deniz
Abstract: Recent emergencies, such as the COVID-19 pandemic have shown how timely information sharing is essential to promptly and effectively react to emergencies. Internet of Things has magnified the possibility of acquiring information from different sensors and using it for emergency management and response. However, it has also amplified the potential of information misuse and unauthorized access to information by untrusted users. Therefore, this paper proposes an access control framework tailored to MQTT-based IoT ecosystems. By leveraging Complex Event Processing, we can enforce controlled and timely data sharing in emergency and ordinary situations. The system has been tested with a case study that targets patient monitoring during the COVID-19 pandemic, showing promising results.